Simulation of the process of silica functionalization in the microreactor - Miroshnychenko, Yuliia; Beznosyk, Yuriy (Eastern-European Journal of Enterprise Technologies, 2015)
In this paper, we performed an analysis of the data on application of the innovative approach for the optimization of functionalized silica materials chemical synthesis in the flow microreactor. A detailed description of such materials is possible with the use of modern techniques and advanced modeling tools. On the basis of the quantum-chemical modeling of molecular clusters we examined the precise structural parameters and adsorptive properties of the investigated substances thatcan be used for water treatment. In accordance with the complexity of the functionalized materials synthesis it has been proved the expediency of the flow microreactor implementation to carry out the process of silica surface functionalization. A comparison between the fundamental advantages of the microdevices with the conventional chemical equipment has been discussed in the context of sustainable manufacturing. Several features that allow contributing flow microreactors to green and sustainable chemical synthesis were presented: process intensification; inherent reactor safety; broader reaction conditions including up-to the explosion regime; faster process development; easier scale-up of production capacity; lower costs for materials, energy and transportation; more flexible response to market demands. By virtue of these potential benefits of microreactors in technological and financial aspects, we showed that miniaturized reaction systems can be used to carry out a synthesis of such innovative materials as adsorbents. By means of the modeling of the functionalization process it is possible to provide clear guidance for the chemical synthesis of substances with useful properties in chemical industry and technology, biochemistry, pharmaceutics and medicine.